2012
DOI: 10.1113/jphysiol.2012.230540
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar modulation of human associative plasticity

Abstract: Paired associative stimulation (PAS) is a method commonly used in human studies of motor cortex synaptic plasticity. It involves repeated pairs of electrical stimuli to the median nerve and transcranial magnetic stimulation (TMS) of the motor cortex. If the interval between peripheral and TMS stimulation is around 21–25 ms, corticospinal excitability is increased for the following 30–60 min via a long term potentiation (LTP)-like effect within the primary motor cortex. Previous work has shown that PAS depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 39 publications
11
154
1
2
Order By: Relevance
“…We cannot tell with certainty if any of these two receptor subtypes was more likely to mediate the observed EtOH effects on LTP-like plasticity. However, it was recently shown that increasing cerebellar excitability by anodal transcranial direct current stimulation or intermittent theta-burst stimulation abolished PAS-induced LTP-like plasticity (Hamada et al, 2012;Popa et al, 2013), but this suppressive effect was seen only with PAS 25ms (ie with the interval between the electrical stimulus to the median nerve and TMS of the contralateral M1 equaling 25 ms) and not with PAS 21.5ms (Hamada et al, 2012). The mean PAS interstimulus interval in our study was 21.9 ms.…”
Section: Drug Effects On Pas Ltp -Induced Ltp-like Increase Of Mep Iomentioning
confidence: 43%
“…We cannot tell with certainty if any of these two receptor subtypes was more likely to mediate the observed EtOH effects on LTP-like plasticity. However, it was recently shown that increasing cerebellar excitability by anodal transcranial direct current stimulation or intermittent theta-burst stimulation abolished PAS-induced LTP-like plasticity (Hamada et al, 2012;Popa et al, 2013), but this suppressive effect was seen only with PAS 25ms (ie with the interval between the electrical stimulus to the median nerve and TMS of the contralateral M1 equaling 25 ms) and not with PAS 21.5ms (Hamada et al, 2012). The mean PAS interstimulus interval in our study was 21.9 ms.…”
Section: Drug Effects On Pas Ltp -Induced Ltp-like Increase Of Mep Iomentioning
confidence: 43%
“…In recent work, we have demonstrated that cerebellar suppression in healthy subjects by transcranial direct current stimulation impairs subsequent motor cortical facilitation by PAS. 26 We therefore speculate that the absent PAS response in tremulous neuropathy patients may reflect cerebellar dysfunction that is also responsible for their impaired EBCC.…”
Section: Figure 2 Short Afferent Inhibition In the 3 Groupsmentioning
confidence: 99%
“…Dystonia might result from cerebellar dysfunction and not destruction, or from abnormal interactions of cerebellar and basal ganglia networks. These networks might interact anatomically at the level of the motor cortex or the striatum, as evidenced by histological tract tracing in animals, 85 animal models of dystonia, 84 and functionally in healthy human volunteers, in whom cortical excitability can be modulated after cerebellar interventions [86][87][88] or after cerebellar degeneration or infarction (S46). The cerebellum might contribute to the deficit in sensorimotor integration recorded in dystonia 89 because it processes proprioceptive information, alters somatosensory thresholds in the cortex, and has a key role in both temporal and spatial discrimination (S47).…”
Section: Dystoniamentioning
confidence: 99%